POLA PEMBELAJARAN KITAB KUNING - Umroatin, Yuli (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
At the beginning of the foundation Nurul Qur'an boarding school, the process of studying the book took place in moscow, because the unavailability of the building to learn. The mosque is used as a learning center of the book. Although in the mosque, but the system has been classical just learning not yet in class. The study of the book is non-formal, so it is held night, day and evening. In relation to the pattern of learning yellow book, the author wanted to reveal more deeply and describe the pattern of learning books in Islamic boarding school Nurul Qur'an. The purpose of this study is as follows: (1) to know and describe the pattern of learning yellow book in Nurul Qur'an Pakunden boarding school, (2) to know and describe the factors supporting and inhibiting the process of learning yellow book in Nurul Qur'an Pakunden boarding school. This research uses interview method, observation and documentation as an instrument in data collection. From the research ahsil, it can be seen that the pattern of learning book in Nurul Qur'an Pakunden boarding school is using the classical system, and pesantren-based and almost the same as the KBK, which prioritizes the competence of santri rather than the material. In addition to prioritizing the competence of santri, also focuses on the formation of students who tafaqquh f? al-D?n. The learning process took place in the classroom and the mosque, inside the mosque because of several factors, including: the morning for formal schooling, the funding factor, the meaning of Islamic student who are less capable of the morning to work, and others. The methods applied are rote, wetonan, sorogan and halaqah / mudzakarah. The book's holy book aims to hone the Islamic student's ability in mastering the book in terms of reading, meaning, and explanation. There are several factors that can influence the success of yellow book learning process is the supporting and inhibiting factors. These factors include individual (internal) and social (external) factors.